2014
DOI: 10.1242/jeb.107128
|View full text |Cite
|
Sign up to set email alerts
|

Forelimb muscle architecture and myosin isoform composition in the groundhog (Marmota monax)

Abstract: Scratch-digging mammals are commonly described as having large, powerful forelimb muscles for applying high force to excavate earth, yet studies quantifying the architectural properties of the musculature are largely unavailable. To further test hypotheses about traits that represent specializations for scratch-digging, we quantified muscle architectural properties and myosin expression in the forelimb of the groundhog (Marmota monax), a digger that constructs semi-complex burrows. Architectural properties mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 56 publications
4
40
0
Order By: Relevance
“…The relatively higher expression of the MHC-2A isoform in the digital flexor muscles seems most appropriate for this functional role in scratch-digging. Future studies of additional species of armadillos are needed verify the significance of MHC-2A expression in the distal limbs; however, these findings are consistent with recent observations in the carpal/ digital flexors of burrowing M. monax (Rupert et al 2015).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The relatively higher expression of the MHC-2A isoform in the digital flexor muscles seems most appropriate for this functional role in scratch-digging. Future studies of additional species of armadillos are needed verify the significance of MHC-2A expression in the distal limbs; however, these findings are consistent with recent observations in the carpal/ digital flexors of burrowing M. monax (Rupert et al 2015).…”
Section: Discussionsupporting
confidence: 83%
“…Similar to other terrestrial scratch-diggers studied (e.g., Gambaryan 1974;Moore et al 2013;Warburton et al 2013;Rupert et al 2015), forelimb muscle mass in D. novemcinctus is concentrated in the limb retractor, elbow extensor, and digital flexor muscle groups. These functional groups combined accounted for over 80 % of total forelimb muscle mass.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, more than any other factor, muscle architecture predicts muscle function (Lieber and Fridén 2000;Ward et al 2009;Lieber and Ward 2011). The importance of muscle fiber architecture has long been recognized and related studies have been widely reported in human and other mammals (Sacks and Roy 1982;Payne et al 2005Payne et al , 2006Williams et al 2007Williams et al , 2008Eng et al 2008;Channon et al 2009;Rupert et al 2014), but seldom in birds. Report on the hind limb of an ostrich by Smith et al (2006) may have been the first comprehensive research on avian muscle architecture.…”
Section: Introductionmentioning
confidence: 99%